1985
DOI: 10.1083/jcb.101.6.2124
|View full text |Cite
|
Sign up to set email alerts
|

Occluding junction structure-function relationships in a cultured epithelial monolayer.

Abstract: Electrical circuit analysis was used to study the structural development of occluding junctions (OJs) in cultured monolayers composed of T84 cells. The magnitude of the increments in transepithelial resistance predicted by such analysis was compared with the magnitude of the measured increments in resistance. Confluent sheets of epithelial cells were formed after cells were plated at high density on collagen-coated filters. Using Claude's OJ strand countresistance hypothesis (1978, J. Membr. Biol. 39:219-232),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
198
1

Year Published

1991
1991
2002
2002

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 384 publications
(205 citation statements)
references
References 33 publications
(49 reference statements)
6
198
1
Order By: Relevance
“…Monolayers exposed to even 1,000 U/ml IFN-'y for 72 h maintain resistances generally exceeding 250-300 ohm.cm 2 (Madara and Stafford, 1989), and we have previously shown that modulation of epithelial resistance in the range of 200-2,000 ohm.cm 2 has little effect on the efficiency of PMN transmigration (Nash et al, 1987). This is likely due to the fact that the relationship between resistance and the flux of solutes, such as those in the size-range of FMLP is asymptotic (Madara and Dharmsathaphorn, 1985;Hecht et al, 1988); that is, at higher resistance values (>200-250 ohm.cm:), large changes in resistance are accompanied by only modest changes in solute flux. The reasons for this are clear when one considers the behavior of a circuit composed of parallel resistances as we have discussed in the past (Madara and Dharmsathaphorn, 1985).…”
Section: Ifn-'y Modulates Pmn Transepithelial Migration In the Apicalmentioning
confidence: 97%
See 3 more Smart Citations
“…Monolayers exposed to even 1,000 U/ml IFN-'y for 72 h maintain resistances generally exceeding 250-300 ohm.cm 2 (Madara and Stafford, 1989), and we have previously shown that modulation of epithelial resistance in the range of 200-2,000 ohm.cm 2 has little effect on the efficiency of PMN transmigration (Nash et al, 1987). This is likely due to the fact that the relationship between resistance and the flux of solutes, such as those in the size-range of FMLP is asymptotic (Madara and Dharmsathaphorn, 1985;Hecht et al, 1988); that is, at higher resistance values (>200-250 ohm.cm:), large changes in resistance are accompanied by only modest changes in solute flux. The reasons for this are clear when one considers the behavior of a circuit composed of parallel resistances as we have discussed in the past (Madara and Dharmsathaphorn, 1985).…”
Section: Ifn-'y Modulates Pmn Transepithelial Migration In the Apicalmentioning
confidence: 97%
“…This is likely due to the fact that the relationship between resistance and the flux of solutes, such as those in the size-range of FMLP is asymptotic (Madara and Dharmsathaphorn, 1985;Hecht et al, 1988); that is, at higher resistance values (>200-250 ohm.cm:), large changes in resistance are accompanied by only modest changes in solute flux. The reasons for this are clear when one considers the behavior of a circuit composed of parallel resistances as we have discussed in the past (Madara and Dharmsathaphorn, 1985). Such sieving characteristics have other implications for the movement of PMN across epithelia (vida infra).…”
Section: Ifn-'y Modulates Pmn Transepithelial Migration In the Apicalmentioning
confidence: 99%
See 2 more Smart Citations
“…Inulin is a high molecular weight (-5,000) inert macromolecule which is normally excluded from cells, and is therefore used as a tracer of extracellular permeability pathways through the intercellular tight junctions, and an indicator of changes in the permeability of this paracellular pathway (Madara & Dharmsathaphorn, 1985). Bidirectional ['4C]-inulin fluxes were determined exactly as for vinblastine sulphate fluxes.…”
Section: Measurement Of Bidirectional Transepithelial [3h]-vinblastinmentioning
confidence: 99%